New for Ukraine records of heterobasidioid fungi - Akulov O.Yu.; Romanchenko O.V. (Ukrainian Botanical Journal, 2025)
The article presents information about three species of heterobasidioid fungi (Eichleriella leucophaea, Mycogloea macrospora, and Platygloea disciformis) that have not been previously registered in Ukraine. Among them, M. macrospora is the rarest mycoparasitic species. Most of the records are reported from Medobory Nature Reserve (Ternopil Region, Western Forest-Steppe). Light microscopy was used for the specimen identification. Based on the analysis of literature sources and personal data of the authors, information about morphological characteristics, distribution, and substrate specialization of the reported fungi is summarized. Additionally, brief historical notes on the taxonomy of these species are provided.